2023
DOI: 10.1021/acs.biochem.2c00690
|View full text |Cite
|
Sign up to set email alerts
|

Design and Biochemical Characterization of Peptidic Inhibitors of the Myb/p300 Interaction

Abstract: The Myb transcription factor is involved in the proliferation of hematopoietic cells, and deregulation of its expression can lead to cancers such as leukemia. Myb interacts with various proteins, including the histone acetyltransferases p300 and CBP. Myb binds to a small domain of p300, the KIX domain (p300 KIX ), and inhibiting this interaction is a potential new drug discovery strategy in oncology. The available structures show that Myb binds to a very shallow pocket of the KIX domain, indicating that it mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Moreover, in vitro studies demonstrated that the mimic induced effects similar to Celastrol in AML cells, while in vivo experiments showed the prolonged survival of mice engrafted with patient-derived AML cells, mirroring the effects observed with Celastrol [ 21 , 79 ]. Encouraged by these promising results, various laboratories are currently engaged in the development of additional MYB-p300 inhibitory compounds [ 80 , 81 , 82 , 83 ].…”
Section: Myb As a Therapeutic Targetmentioning
confidence: 99%
“…Moreover, in vitro studies demonstrated that the mimic induced effects similar to Celastrol in AML cells, while in vivo experiments showed the prolonged survival of mice engrafted with patient-derived AML cells, mirroring the effects observed with Celastrol [ 21 , 79 ]. Encouraged by these promising results, various laboratories are currently engaged in the development of additional MYB-p300 inhibitory compounds [ 80 , 81 , 82 , 83 ].…”
Section: Myb As a Therapeutic Targetmentioning
confidence: 99%
“…This compound showed potent Hsp90 inhibition and represented a good candidate for the treatment of proliferation diseases. 72…”
Section: Anticancer Activity Of Fluorinated Heterocyclesmentioning
confidence: 99%
“…MYB is a critical transcriptional dependency of acute myeloid leukemia (AML) 11,18,28,29 , where it has been a longterm focus of therapeutic efforts [30][31][32][33][34][35][36][37] , making AML a relevant context for functional characterization of MYB inhibitors. We therefore began by engineering a chemical degron model of MYB in AML cells.…”
Section: A Degron Model Reveals Direct Gene-regulatory Functions Of Mybmentioning
confidence: 99%